ADDIE-Based Design Research of Institutional Batik at Ma Chung University - Amar Ma'ruf Stya Bakti; Didit Prasetyo Nugroho (Universitas Negeri Medan, 2025)
Batik has increasingly been adopted by higher education institutions as a medium of institutional identity; however, existing studies on institutional batik largely remain descriptive, emphasizing aesthetic outcomes rather than examining the systematic process through which institutional philosophical values are translated into visual form. This research addresses that gap by investigating the development of Ma Chung University’s batik motif through a Research and Development (R&D) approach using the ADDIE model, positioned as a practice-based design research framework. The study aims not only to produce a batik motif, but to formulate a structured design process that articulates philosophical values and campus identity into visual elements such as motifs, composition, and color systems. Data were collected through literature review, institutional document analysis, in-depth interviews, observation, and user evaluation. Qualitative data were analyzed interpretatively to map philosophical values into visual symbols, while quantitative data were analyzed descriptively to assess design acceptance. The results demonstrate that the “Tugu Ma Chung Tirta Harmoni” batik motif functions as a visual system of institutional representation, rather than merely a decorative artifact. The study contributes academically by offering a replicable R&D-based model for institutional batik design, extending discussions in art and design research on visual identity, practice-based methodology, and culture-based design in higher education contexts.